1998
DOI: 10.1161/01.str.29.7.1417
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Ischemic Brain Injury by Topical Application of Glial Cell Line–Derived Neurotrophic Factor After Permanent Middle Cerebral Artery Occlusion in Rats

Abstract: Background and Purpose-Glial cell line-derived neurotrophic factor (GDNF) plays important roles in the survival and recovery of some mature neurons under pathological conditions. However, the effect of GDNF in ameliorating ischemic brain injury has not been well documented. Therefore, we investigated a possible effect of GDNF on the changes of infarct size, brain edema, DNA fragmentation, and immunoreactivities for caspases after permanent middle cerebral artery occlusion (MCAO) in rats. Methods-For the estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
87
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(93 citation statements)
references
References 41 publications
5
87
0
1
Order By: Relevance
“…The mechanisms by which GDNF exerts its neuroprotective effect are diverse, and recent evidence demonstrates that the rescue and repair of injured neurons is a consequence of an antiapoptotic action of GDNF. Indeed, GDNF has been shown to up-regulate Bcl-2 and Bcl-X L levels in rat mesencephalic neurons subjected to apoptosis, resulting in a reduction of caspase activation (Kitagawa et al, 1998;Sawada et al, 2000). The present investigation not only confirms these antiapoptotic properties of GDNF, but further elucidates the cell organelles in which the apoptosis-regulatory proteins are controlled.…”
Section: Figsupporting
confidence: 77%
See 1 more Smart Citation
“…The mechanisms by which GDNF exerts its neuroprotective effect are diverse, and recent evidence demonstrates that the rescue and repair of injured neurons is a consequence of an antiapoptotic action of GDNF. Indeed, GDNF has been shown to up-regulate Bcl-2 and Bcl-X L levels in rat mesencephalic neurons subjected to apoptosis, resulting in a reduction of caspase activation (Kitagawa et al, 1998;Sawada et al, 2000). The present investigation not only confirms these antiapoptotic properties of GDNF, but further elucidates the cell organelles in which the apoptosis-regulatory proteins are controlled.…”
Section: Figsupporting
confidence: 77%
“…Upregulation of GDNF mRNA in rat brains has been shown to occur following excitotoxicity induced by glutamate (Ho et al, 1995) or kainate (Humpel et al, 1994). GDNF has been shown to protect neurons against oxidative stress in cultured mesencephalic neurons and glial cells (Iwata-Ichikawa et al, 1999), against ischemic/hypoxic-induced brain injury in neonatal rats (Ikeda et al, 2000), after brain injury following permanent middle cerebral artery occlusion in rats (Kitagawa et al, 1998), and in primate models of Parkinson's disease (Kordower et al, 2000). The mechanisms by which GDNF exerts its neuroprotective effect are diverse, and recent evidence demonstrates that the rescue and repair of injured neurons is a consequence of an antiapoptotic action of GDNF.…”
Section: Figmentioning
confidence: 99%
“…Previously, amelioration of ischemic brain injury when GDNF was applied after middle cerebral artery occlusion was demonstrated in a rodent model. [15][16][17] Moreover, the neuroprotective activity of adenovirus-mediated GDNF gene transfer, which is minimally invasive and maintains hGDNF protein production, has also been reported in focal cerebral ischemia, 18,19 global ischemic brain damage, 20 and spinal cord ischemic injury. 21 In the adult rat ear, GDNF mRNA has been detected using in situ hybridization 22 and RT-PCR, 23 and immunohistochemistry has been used to localize GDNF protein 24 in the organ of Corti.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has demonstrated that GDNF diminishes ischemia-induced free-radical release by inhibiting neuronal free-radical synthesis during ischemia, 16 or by reducing neuronal caspase activity in the damaged brain. 17 It has been proposed that free radicals or caspase reactivity in the ear are responsible for ischemic damage, because antioxidants have a protective effect on the CAP threshold shift induced by cochlear ischemia. 29,30 In addition, recent experimental studies have shown that ischemia-reperfusion injury of the inner ear appears to be restricted to IHCs, which is closely related to glutamate neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] These neurotrophic factors may be valuable as candidates for use in therapy of neurodegenerative diseases. It has been reported that the neuronal cell death induced by ischemic injury was prevented by the administration of GDNF [13][14][15] and NGF [16][17][18] proteins. However, the usefulness of such protein factors in patients is limited because of their poor bioavailability and short half-lives.…”
mentioning
confidence: 99%